Review of World Bank's Experience with Country-Level Health System Analysis - Bitrán, Ricardo; Gómez, Paulina; Escobar, Liliana; Berman, Peter (World Bank, Washington, DC, 2013)
The World Bank often carries out in-depth analysis of the conditions and challenges facing different sectors in our client countries as a contribution to developing the analytical and information base for lending, policy dialogue, and more in-depth analytical work. In the health sector, we have identified a substantial body of this type of work focusing on analyzing the performance of health systems, its causes, and potential strategies for performance improvement. The Bank's 2007 Health, Nutrition and Population (HNP) strategy emphasizes the importance of our work on health system strengthening. HSA is often the analytical foundation of this work in countries. This paper reviews a sample of HSAs, 12 major studies carried out since 2000 across all Bank regions. Using the health systems framework of the flagship program on health sector reform and sustainable financing, a comparable synopsis of each study has been prepared in a simple two page chart which traces the analysis from measures of health system performance to its causes and then from policy 'control knobs' to proposals for reform which are intended to improve that performance. Several key questions about the conceptual basis, content, process, and results of the Bank's work on HSA are investigated. The review finds that most of our HSAs make use of sound analytical frameworks that link performance to a causal analysis and derive policy recommendations and reform strategies from that analysis.